Patient-posture and Ileal-intubation during colonoscopy (PIC): a randomized controlled open-label trial - Ahammed, Sk Mahiuddin; Das, Kshaunish; Sarkar, R.; Dasgupta, J.; Bandopadhyay, S.; Dhali, G. K. (Endoscopy International Open, 2014)
Background and aims: Patient’s posture change is commonly employed by a colonoscopist to achieve complete examination. We studied whether patient’s posture (left-lateral decubitus vs supine) influenced the success rate of ileal intubation.Patients and methods: In this prospective open-label randomized study performed in the Endoscopy Suite of a tertiary-care center, all adult outpatients referred for colonoscopy, in whom cecal intubation was achieved and who satisfied predefined inclusion criteria, were randomized to undergo ileal intubation in either of the above two postures. Colonoscopy (EC-201 WL, Fujinon) was performed after overnight poly-ethylene-glycol preparation, under conscious sedation and continuous pulse-oxymetry monitoring. After confirming cecal intubation, patients were randomized for ileal intubation. Success was defined by visualization of ileal mucosa or villi (confirmed by digital photography) and was attempted until limited by pain and/or time of ≥ 6 min.Results: Of 320 eligible patients, 217 patients (150 males) were randomized, 106 to left-lateral decubitus and 111 to supine posture. At baseline, the two groups were evenly matched. Successful ileal intubation was achieved in 145 (66.8 %) patients overall, significantly higher in the supine posture (74.8 % versus 58.5 %; P = 0.014). On multivariate analysis, supine posture (P = 0.02), average/good right-colon preparation (P < 0.01), non-thin-lipped ileocecal (IC) valve (P < 0.001) and younger age (P = 0.02) were independent predictors of success. Positive ileal findings were recorded in 13 (9 %) patients.Conclusion: Ileoscopy is more successful in supine than in left-lateral decubitus posture. Age, bowel preparation and type of IC valve also determine success.